(3GdeMGceGJ Hjf TQMi GdETGQGJs - (3GdbWH GdJMJGfj , eMeO (B( (3eMehO (B) (3Hf eMeO GdQGRj, CHh YHO Gddg, bWH GdOjf CHh YHO Gddg GdJMJGfj,J (B766 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3hEjGc GSJjYf jG cQje bGd GdTGQM CMSf Gddg EcQGeg GdMeO ddg GdPi habfG dGaJJGM GdebGd s
(3BNQgG (B:s
(3gPG eG JdNU dOjfG ai TQM GdTQM HGdGacGQ GdeJhGdjI agh HgPG GdcJGH GhLH Gdfgi Yf EVGYJg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3TQMi GdGTGQGJ dfUjQ GdOjf eMeO Hf GdMSf GdWhSi J SfI (B679 (3haNQ GdOjf eMeO Hf YeQ GdQGRi J SfI (B606s
(3hbO cJHgG bWH GdOjf HETGQI ef bWH GdOjf GdTjQGRis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B38 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B215s
Keywords: (3GdadSaI hGdefWbs